1981
DOI: 10.1016/0033-5894(81)90129-0
|View full text |Cite
|
Sign up to set email alerts
|

The Selection of Sites for Paleovegetational Studies

Abstract: The judicious selection of sites for paleovegetational and paleoclimatic studies permits paleoecologists to answer specific research questions that go beyond primary descriptions of past vegetation. We present a model that describes the relationship between basin size and pollen source area and predicts the proportions of local, extralocal, and regional pollen sampled by lake basins of different size. The distinctive sampling properties of lakes, peats, and small hollows can be exploited to provide details of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
529
1
13

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 910 publications
(561 citation statements)
references
References 51 publications
7
529
1
13
Order By: Relevance
“…Pollen has many dispersal methods, including wind, water and animal vectors, all of which have the capability to transport pollen outside of the local area. Tauber ( 1965, in Moore et al 1991 Jacobson and Bradshaw (1981) Pollen analysis of surface sediments has also shown that some pollen types may be overor under-represented in the pollen record. This is due to differences in the amount of pollen produced and the methods in which the pollen is dispersed.…”
Section: Pollen Dispersalmentioning
confidence: 99%
“…Pollen has many dispersal methods, including wind, water and animal vectors, all of which have the capability to transport pollen outside of the local area. Tauber ( 1965, in Moore et al 1991 Jacobson and Bradshaw (1981) Pollen analysis of surface sediments has also shown that some pollen types may be overor under-represented in the pollen record. This is due to differences in the amount of pollen produced and the methods in which the pollen is dispersed.…”
Section: Pollen Dispersalmentioning
confidence: 99%
“…About thirty years ago, palynological researchers began to produce quantitative estimates of a pollen source area for basins of different sizes (Jacobson and Bradshaw, 1981). The Prentice model of pollen dispersal and deposition (Prentice, 1985) allowed simulation of aerial pollen taphonomy to be used to estimate quantitative source areas for individual pollen types (Prentice et al, 1987), defined as the radius around the basin from which a defined percentage of the pollen type originated.…”
Section: Introductionmentioning
confidence: 99%
“…Although these study sites have provided detailed information about the nature and timing of human impact it is difficult to make inferences about the spatial extent of human impact on the landscape (Edwards 1979;Brown 1999). This is due to the scale of their pollen source areas, which is likely to be regional in nature (Jacobsen and Bradshaw 1981;Prentice 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The question of the size of the pollen source area has been discussed by Jacobsen and Bradshaw (1981), and more recent attempts have been made to quantify aspects of pollen source area (Prentice 1985;Sugita 1993Sugita , 1994Sugita , 1998. For sites within the size range used in this study, the local and extra-local relevant source area should be in the order of hundreds of metres (Jacobsen and Bradshaw 1981). The sites are located beyond the present-day margins of the enclosed landscape on the southern upland fringes of Greater Exmoor (around 300 to 340 m OD).…”
Section: Introductionmentioning
confidence: 99%